2021
DOI: 10.7554/elife.69454
|View full text |Cite
|
Sign up to set email alerts
|

Exosome component 1 cleaves single-stranded DNA and sensitizes human kidney renal clear cell carcinoma cells to poly(ADP-ribose) polymerase inhibitor

Abstract: Targeting DNA repair pathway offers an important therapeutic strategy for Homo sapiens (human) cancers. However, the failure of DNA repair inhibitors to markedly benefit patients necessitates the development of new strategies. Here, we show that exosome component 1 (EXOSC1) promotes DNA damages and sensitizes human kidney renal clear cell carcinoma (KIRC) cells to DNA repair inhibitor. Considering that endogenous source of mutation (ESM) constantly assaults genomic DNA and likely sensitize human cancer cells t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…In addition, upregulation of EXOSC4 and EXOSC5 expression has been reported in colorectal cancer, in which upregulated expression of EXOSC5 was associated with a worse prognosis [113,114]. A correlation between high EXOSC1 expression and poor prognosis has been reported in kidney renal clear cell carcinoma [19]. Such relationships have also been observed for various core exosome components in mantle cell lymphoma [115].…”
Section: Rna Exosome and Cancermentioning
confidence: 82%
See 2 more Smart Citations
“…In addition, upregulation of EXOSC4 and EXOSC5 expression has been reported in colorectal cancer, in which upregulated expression of EXOSC5 was associated with a worse prognosis [113,114]. A correlation between high EXOSC1 expression and poor prognosis has been reported in kidney renal clear cell carcinoma [19]. Such relationships have also been observed for various core exosome components in mantle cell lymphoma [115].…”
Section: Rna Exosome and Cancermentioning
confidence: 82%
“…A recent proteomic analysis of cell cycle-dependent protein interactions suggests that the dynamics of EXOSC components can be divided into three groups: (1) PH ring components (EXOSC4-9) and EXOSC2, (2) EXOSC1 and EXOSC3, and (3) EXOSC10 [17]. EXOSC1, EXOSC3, and EXOSC10 are less stably associated with the core exosome complex than the other EXO9 subunits, possibly suggesting that these proteins have independent functions outside of the exosome complex [18,19]. Indeed, the exosome-independent functions of EXOSC1 have been suggested [19].…”
Section: Structure Of Rna Exosomementioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of DNA repair by radiation therapy combined with veliparib accelerates induction of tumor cell senescence and induces expression of immune stimulators to activate cytotoxic T lymphocytes and mediate antitumor response (104). Patients with ccRCC with high exosome component 1 show poor prognosis; exosome component 1 cleaves single-stranded DNA and sensitizes human ccRCC cells to PARPis (105).…”
Section: Ddr Genes and Precision Treatment Of Renal Cancermentioning
confidence: 99%
“…Apart from the RNA degradation function of the EXOSC, its components are also associated with carcinogenesis. It has been reported that EXOSC1 could cleave single-stranded DNA and sensitize human kidney renal clear cell carcinoma cells to poly (ADP-ribose) polymerase inhibitors [ 11 ]. Additionally, the enhancing expression of EXOSC2 directly regulated by tRNAGluUUC is closely related to breast cancer metastasis [ 12 ], while EXOSC3 and EXOSC4 can trigger the development of colonic and colorectal cancer, respectively [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%